Identifying a new subtype of multiple sclerosis. (December 2018) - Trapp, Bruce D; Ontaneda, Daniel
Dr Bruce Trapp and Dr Daniel Ontaneda speak to Laura Dormer, Commissioning Editor: Bruce D Trapp, PhD, is a Chair of the Department of Neurosciences at the Lerner Research Institute, Cleveland Clinic (OH, USA) and Professor of Molecular Medicine at Case Western Reserve University (OH, USA). Dr Trapp received his PhD from Loyola University Stritch School of Medicine in Chicago (IL, USA). Dr Trapp's research investigates the cause of neurological disability in multiple sclerosis patients, cellular mechanism of brain repair in neurodegenerative diseases and the molecular biology of myelination in the central and peripheral nervous systems. Daniel Ontaneda, MD, is a staff neurologist at the Cleveland Clinic Mellen Center for Multiple Sclerosis. Dr Ontaneda earned his MD from the Universidad Católica del Ecuador and MSc in clinical research from Case Western Reserve University. He completed a postdoctoral fellowship at Baylor College of Medicine, followed by neurology and neuroimmunology training at the Cleveland Clinic. His specialties include acute disseminated encephalomyelitis, Devic's disease (neuromyelitis optica), multiple sclerosis, neuroimmunology, optic neuritis and transverse myelitis.